The effects of different sizes of coarse aggregate on strength of porous concrete - Nik Muhamad Faizal Nik Mood (School of Environmental Engineering, University Malaysia Perlis, 2016)
This research presents the study on the effect of different sizes of coarse aggregate on strength of porous concrete. The objective of this study was to determine the optimum size of coarse aggregate to be used as porous concrete effectively, to study the physical and mechanical properties of porous concrete using different sizes of coarse aggregate and to observe the crack behaviour of porous concrete with respect to compressive test. This study used cube with size 100 mm x 100 mm x 100 mm as samples. Some test was conducted to achieve objective that had been chosen. Test was conducted at two states which is fresh state and hardened state. Slump test was conducted for fresh state of porous concrete. Average result for slump test is 15 mm. For hardened state, three tests was done in order to achieve second objectives of this study which is to study the physical and mechanical properties of porous concrete using different sizes of coarse aggregate. All samples has undergone curing process in curing tank for 7-days and 28-days. Compressive strength test was conducted and highest result for this test was 4.7 N/mm2. In addition, straight observation was done in order to observe crack behaviour during compressive strength test. The observation was done in order to achieve third objective of this study. Then, for water absorption test, the average result was 7.3%. Density result for this study 1929 kg/m3 for range 16-19.5 mm sizes of coarse aggregate. Result and data was collected and analyse in order to achieve the objectives that had been chosen.